Penerapan Strategi Pemasaran Digital Melalui Media Sosial Instagram Dalam Meningkatkan Penjualan Pada Arunazma - Vania Regita Lailia; Jojok Dwiridotjahjono (Jurnal of Management and Social Sciences, 2023)
This study aims to determine digital marketing strategies through Instagram social media in increasing sales at the Arunazma Online Shop. This type of research is descriptive research. Data sources will be taken from documents, observation results, and interview results. The digital marketing strategy carried out by Arunazma includes the planning, implementation and monitoring stages to increase sales at Arunazma. The obstacles faced by Arunazma in implementing digital marketing, namely delays in delivery and lack of human resources. Arunazma can overcome these obstacles by accelerating the packing process and adding employees to make it more efficient. The positive impact of implementing digital marketing by Arunazma is that digital marketing can increase sales of products in the Arunazma Online Shop.